One-Stop Management with Perfusion for Transfer Patients with Stroke due to a Large-Vessel Occlusion: Feasibility and Effects on In-Hospital Times - Brehm, A.; Tsogkas, I.; Maier, I.L.; Eisenberger, H.J.; Yang, P.; Liu, J.-M.; Liman, J.; Psychogios, M.-N. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: In-hospital time delays lead to a relevant deterioration of neurologic outcomes in patients with stroke with large-vessel occlusions. At the moment, CT perfusion is relevant in the triage of late-window patients with stroke. We conducted this study to determine whether one-stop management with perfusion is feasible and leads to a reduction of in-hospital times.MATERIALS AND METHODS: In this observational study, we report the first 15 consecutive transfer patients with stroke with externally confirmed large-vessel occlusions who underwent flat panel detector CT perfusion and thrombectomy in the same room. Preinterventional imaging consisted of noncontrast flat panel detector CT and flat panel detector CT perfusion, acquired with a biplane angiography system. The flat panel detector CT perfusion was used to reconstruct a flat panel detector CT angiography to confirm the large-vessel occlusions. After confirmation of the large-vessel occlusion, the patient underwent mechanical thrombectomy. We recorded time metrics and safety parameters prospectively and compared them with those of transfer patients whom we treated before the introduction of one-stop management with perfusion.RESULTS: Fifteen transfer patients underwent flat panel detector CT perfusion and were treated with mechanical thrombectomy from June 2017 to January 2019. The median time from symptom onset to admission was 241 minutes. Median door-to-groin time was 24 minutes. Compared with 23 transfer patients imaged with multidetector CT, it was reduced significantly (24 minutes; 95% CI, 19–37 minutes, versus 53 minutes; 95% CI, 44–66 minutes; P < .001). Safety parameters were comparable between groups.CONCLUSIONS: In this small series, one-stop management with perfusion led to a significant reduction of in-hospital times compared with our previous workflow.FPDCTflat panel detector CTICHintracranial hemorrhageIQRinterquartile rangeLVOlarge-vessel occlusionMDCTmultidetector CT